Electroporation as a Solvent-Free Green Technique for Non-Destructive Extraction of Proteins and Lipids From Chlorella vulgaris - Eleršek, Tina; Flisar, Karel; Likozar, Blaž; Klemenčič, Marina; Golob, Janvit; Kotnik, Tadej; Miklavčič, Damijan (Frontiers in Bioengineering and Biotechnology, 2020)
Proteins extracted from microalgae for food, personal care products and cosmetics must be of high purity, requiring solvent free extraction techniques despite their generally considerably lower protein yield and higher energy consumption. Here, three such approaches for green extraction of proteins from Chlorella vulgaris were evaluated: ultrasound, freeze thawing, and electroporation; chemical lysis was used as positive control (maximal achievable extraction), and no extraction treatment as negative control. Compared to chemical lysis, electroporation yielded the highest fraction of extracted protein mass in the supernatant (≤ 27%), ultrasound ≤ 24%, and freeze thawing ≤ 15%. After a growth lag of several days, electroporated groups of algal cells started to exhibit growth dynamics similar to the negative control group, while no growth regeneration was detected in groups exposed to ultrasound, freeze thawing, or chemical lysis. For electroporation as the most efficient and the only non destructive among the considered solvent free protein extraction techniques, simultaneous extraction of intracellular algal lipids into supernatant was then investigated by HPLC, proving relatively low yield (≤ 7% of the total algal lipid mass), yet feasible for glycerides (tri-, di-, and mono-) as well as other fatty acid derivatives. Our results show that electroporation, though lower in extraction yields than chemical lysis or mechanical disintegration, is in contrast to them a technique for largely debris-free extraction of proteins from microalgae, with no need for prior concentration or drying, with feasible growth regeneration, and with potential for simultaneous extraction of intracellular algal lipids into the supernatant.